Idea Generation through Employee Suggestion System - Islam, Rafikul (IIUM Journal of Case Studies in Management, 2019)
Today having critical thinking and creativity are two essential requirements of any employee working at any level of any organisation. The reason is obvious. Those are required for product innovation and developing a new, a more cost-effective process of delivery. Managers need to make sure that they provide all the necessary support to the employees so that they become the agent of change through innovation. Here lies the importance of implementing an employee suggestion system. A carefully crafted and implemented employee suggestion system may be a catalyst for creating an organisation wide culture of innovation.